Evolución y perspectivas de la industria de flores frescas cortadas colombianas para exportación (2020)
In this document, a documentary investigation is carried out on how evolution has been, what the current situation us and what to prospects may be for the Colombian fresh cut flowers industry has been evoling for export, taking key milestones in what has been happening of the years and the evolution of the indsutry, such as the creation of Asocolflores. In the second chapter, thanks to a historicist approach, it is posible to understand the current situation of the Colombian fresh cut flowers for export industry, the figures are shown in the course of the last years of the sector at the national level and additionally a topic od magna is addressed relevance, as is the impact that the covid-19 is having on this agricultural ítem that has so many currencies and social impact has form Colombia. In the third chapter, the perspectives of the Colombian fresh cut flowers for export industry are presented, mentioning the challenges and the objective markets that the Colombian Association of Flowers Exporters is considering. Finally, the respective conclusions are made on the topic coveres and some recommendations are made for future studies on this topic.